2007
DOI: 10.1007/s11145-007-9101-y
|View full text |Cite
|
Sign up to set email alerts
|

Early phonological and lexical markers of reading disabilities

Abstract: Phonological and lexical characteristics of 30-month-old children's spontaneous language samples were examined as indicators of later reading outcome. Participants were 27 children, 10 children with reading disability and 17 children without reading disability. Of the non-disabled readers, 7 were at high familial risk for reading disability, and 10 came from families with no history of reading difficulties. Children later identified as reading disabled at second grade and beyond demonstrated narrower lexical d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…Specifically, we found that children with the strongest early reading skills at year-end had improved the most in production accuracy of the Late-8 sounds (which include a high proportion of fricatives) and specifically of fricatives. Although none of the studies conducted to date (Keren-Portnoy et al, 2010; Mann & Foy, 2007; Smith, 2009), including our own, can provide causal conclusions, collectively they do suggest that perhaps language use, and, in this case, experience with certain kinds of speech sound productions, may be associated with robust representations of phonemes associated with early reading development. Although speech production skills most likely reflect qualitative aspects of phoneme representations, our findings, combined with that of other researchers, raise the possibility of great importance to early reading interventionists, that at least a bidirectional relationship might exist between expressive speech production experiences and the development of robust receptive phoneme representations.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…Specifically, we found that children with the strongest early reading skills at year-end had improved the most in production accuracy of the Late-8 sounds (which include a high proportion of fricatives) and specifically of fricatives. Although none of the studies conducted to date (Keren-Portnoy et al, 2010; Mann & Foy, 2007; Smith, 2009), including our own, can provide causal conclusions, collectively they do suggest that perhaps language use, and, in this case, experience with certain kinds of speech sound productions, may be associated with robust representations of phonemes associated with early reading development. Although speech production skills most likely reflect qualitative aspects of phoneme representations, our findings, combined with that of other researchers, raise the possibility of great importance to early reading interventionists, that at least a bidirectional relationship might exist between expressive speech production experiences and the development of robust receptive phoneme representations.…”
Section: Discussionmentioning
confidence: 53%
“…Phonological processing skills appear to be linked with the pattern of errors in phoneme production prior to school entry (e.g., speech errors, Keren-Portnoy, Vihman, DePaolis, Whitaker, & Williams, 2010; Mann & Foy, 2007; Preston & Edwards, 2010; Rvachew & Grawburg, 2006; Smith, 2009). Smith found that children who later developed reading problems (in second grade and beyond) had used phonologically less complex utterances in spontaneous speech at 30-months old than children with normal reading development.…”
Section: Introductionmentioning
confidence: 99%
“…One recent study demonstrated the utility of examining different aspects of vocabulary acquisition in young children in relation to reading acquisition. Lambrecht Smith (2009) reported that children with (versus without) reading disabilities in grade 2 had produced fewer different words and had lower phonological complexity ratings for their word productions at 30 months of age, and suggested that these vocabulary indices may be early markers of reading disabilities. Another possibility is that a third variable, such as the lower level auditory processes indicated in reading difficulties (e.g., Fraser, Goswami, Conti-Ramsden, 2010;Goswami et al, 2002) may cause difficulties for children to both process less common sound patterns and to acquire reading skills in an alphabetic orthography.…”
Section: Discussionmentioning
confidence: 99%
“…Early speech production is perhaps best defined as “utterances of speech as well as other (nonmeaningful) utterances that could be said to be phonotactically well-formed for some natural or potential natural language” [ 14 ]. Early speech production is an informative metric that is directly related to later outcomes, such as lexical development [ 15 , 16 , 17 ], phonological awareness [ 18 ], letter-sound correspondence [ 9 ] and later reading outcomes [ 19 , 20 , 21 , 22 ]. In fact, early speech production is related to how young children learn new words [ 17 ] as well as the strength of their phonological memory [ 23 ].…”
Section: Introductionmentioning
confidence: 99%